The Relationship Between Body Weight and Stress and Nutritional Status in Turkish Women - Sanlier, N.; Unusan, N. (Pakistan Journal of Nutrition, 2007)
The aim of this study was to examine the effects of body weight on stress and nutrition in women. Data were gathered from 889 women living in Turkey. The participants were selected randomly. Women were informed that the purpose of the study was to gather information on stress and nutrition and each participant attended a face-to-face interview. Subjects were administered a questionnaire containing demographic profile, anthropometric measurements, daily energy and macro-nutrients intakes, Stress Scale were used for descriptive purposes. Stress Symptom Scale, Stress Related Factors, Susceptibility to Stress Scale and Total Score were significantly associated with Body Mass Index (BMI) and daily energy and nutrients intake. Underweight and obese women had higher stress scores than normal weight women (p<0.0001). Normal weight women had a higher level of stress susceptibility to stress scale than underweight and obese women (p<0.0001). In addition, it was found that there was a correlation between women`s daily energy and nutrient consumption and their stress-related factors, stress symptoms scale, susceptibility to stress scale and total stress scores (p<0.05 and p<0.0001). The results suggest that, increased stress was strongly associated with body composition and daily energy and nutrients intake among Turkish women.